Anti-adhesion therapy, a promising alternative in the infections treatment - Waleed Madle; Mohammed Ajeel; Muhammad Alkataan; Akram Ajeel; Wijdan Abd-alwahab (University of Mosul, 2018)
Objective: Antibiotic resistance (AR) represents one of the most important health problems worldwide due to the fact that it significantly lowers the number of effective antibacterial agents. Many mechanisms were studied to reduce emerge of AR, one of these is the use of Anti-adhesion Methods: keywords were used to search Most of the subject available articles. Following that, a grammatical examination was done for the vocabulary associated with the literature review. Results: Anti-adhesion agents represent vital approach to stop or treat bacterial infections. As these agents focus on bacterial virulence and pathogenicity properties (e.g. adhesion and colonization).These agents considered a perfect alternative for an antibiotic, with the infectious process inhibiting advantage in the first step to reduce the damage. These agents inhibit bacteria attachment to the surface of the host cell through interfering with the assembly of host receptor, bacteria-host cell assembly or adhesion biosynthesis. Bacterial adhesions antibodies can prevent surface epitopes required for bacteria-host cell attachment by the application of anti-adhesion strategy to decrease AR or reduce the need for the effective antibiotic doses .Conclusions: Anti-adhesion therapy includes efforts for preventing adherence, reduces virulence, and biofilm formation. These have advantages over classical antibiotics through blocking pathogenicity without destroying bacteria and it also have a synergistic effect when applied with antibiotics